A Pharmacological Overview of Alpinumisoflavone, a Natural Prenylated Isoflavonoid - Ateba, Sylvin Benjamin; Mvondo, Marie Alfrede; Djiogue, Sefirin; Zingué, Stéphane; Krenn, Liselotte; Njamen, Dieudonné (Frontiers in Pharmacology, 2019)
Over the last decade, several studies demonstrated that prenylation of flavonoids enhances various biological activities as compared to the respective non-prenylated compounds. In line with this, the natural prenylated isoflavonoid alpinumisoflavone (AIF) has been explored for a number of biological and pharmacological effects (therapeutic potential). In this review, we attempt to summarize the current information and health-promoting properties of AIF. Reported data evidenced that AIF has a multi-therapeutic potential with anti-osteoporotic, anti-oxidant and anti-inflammatory, anti-microbial, anti-cancer, estrogenic and anti-estrogenic, anti-diabetic and neuroprotective properties. However, research on these aspects of AIF is not sufficient and somehow need to be reevaluated using more appropriate methods and methodology. Further series of studies are therefore needed to enrich the knowledge of these pharmacological effects. Overall, despite the drawbacks of studies recorded, AIF exhibits a potential as drug candidate.